Counseling Skills Training for Service Officers of Women's Empowerment and Child Protection Consultation Institute (LKP3A) in Pekalongan Regency - Esti Zaduqisti; Purnomo Rozak; Teddy Dyatmika; Syamsul Bakhri (Islamic Studies Journal for Social Transformation, 2019)
LKP3A counselor in terms of quality and quantity is still very lacking. One of the indications is there are still many unskillful bachelor degree graduates that work as counselors. Thus, there is a need for assistance and empowerment to meet the needs of the community. This community empowerment program aims to improve knowledge and counseling skills that are still relatively minimal for mentors at LKP3A Fatayat Nadhalatul Ulama Pekalongan. This research is a participatory action research (PAR) with a qualitative approach. This research was carried out for 1 year in the NU building in Pekalongan. The subjects of this study were divided into two community categories namely the Core Trainer Team (TIP) and LKP3A Women's Citizens (WP). Counseling skills training is carried out through three activities, namely planning, implementation, and evaluation monitoring activities. The results of this research show that after LKP3A counselors received training and mentoring, it showed many changes, including being able to understand ethical principles for counseling and paying attention to risk management; able to bring up a friendly attitude; empathize; want to listen to clients; understand and appreciate individual differences. The counselor provides services based on these differences. The focus on the client is greater. The counselor understands her position as a counselor, able to integrate theory into counseling practice, able to evaluate the course of counseling both in the process and results.